Design science at the intersection of physical and virtual design : 8th International Conference, DESRIST 2013, Helsinki, Finland, June 11-12, 2013. Proceedings - Hekkala, Riitta; Ram, Sudha; Rossi, Matti; Brocke, Jan (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 8th International Conference on Design Science Research in Information Systems and Technology, DESRIST 2013, held in Helsinki, Finland, in June 2013. The 24 full papers, 8 research-in-progress papers, 12 short papers, and 8 poster abstracts were carefully reviewed and selected from 93 submissions. The papers are organized in topical sections on system integration and design; meta issues; business process management and ERP; theory development; emerging themes; green IS and service management; method engineering; papers describing products and prototypes; and work-in-progress papers.